Latinxs Unidos: Futurism and Latinidad in United States Latinx Hip-Hop. Issue 1 (March 2020) - Taylor, Taryne Jade
Abstract : Music has long been one of the mainstays of Afrofuturism and much Afrofuturist music is directly science fictional. Mainstream Afrofuturist hip-hop artists, such as Jay-Z in his 2018 "Family Feud" music video (directed by Ava DuVernay), employ common tropes from science fiction, placing Afrofuturist hip-hop firmly within the genre. Like Jay-Z, Latinx hip-hop artists such as Cypress Hill, Pitbull, Calle 13, and Los Rakas draw from the rich tradition of Afrofuturism, but more indirectly. Rather than including explicitly science fictional tropes, Latinx Futurist hip-hop engages with Afrofuturist ontologies to construct a unifying, utopian vision of Latinidad in the United States. Through hip-hop, these artists engage with a larger movement of Latinx Futurism, using science fiction as a means of consciousness raising and decolonialization, much as creators of Afrofuturism and Indigenous Futurism have done. Fighting against the dominant racist, imperialist narrative of Latin America, the United States, and even their own US Latinx communities, these artists imagine a unified, powerful, and decolonized Latinx America.